Structural Abnormalities on MRI in Cases with Epilepsy - Kaushik, Gaurav; Madan Manmohan (Asian Journal of Medical Radiological Research, 2020)
Introduction: Many treatable anatomical abnormalities of the brain can cause seizures. The present study was done to determine the role of MRI for evaluation of patients with epilepsy. Subjects and Methods: Patients who presented to our hospital with history of epilepsy. i.e two or more episodes of unproved seizures 24 hours apart, underwent MRI study to assess for abnormalities. Patients of either gender and all age groups who were referred to our department for MRI study were included. Results: Generalized tonic clonic seizures were present in 86% of the population and rest had partial seizures. Using MRI, we arrived at a diagnosis as a cause of seizure in 51.3% of the patients and rest of the 48.7% had a normal MRI study. The most common pathology detected on MRI was infarct with gliosis (24.7%). Less common pathology detected were neurocysticercosis (6.7%), brain atrophy (5.3%), tuberculoma (3.3%), venous thrombosis (2.7%), developmental malformations (2.7%), glioma (1.3%), cavernoma (1.3%), tuberous sclerosis (1.3%), meningioma (0.7%), cerebral abscess (0.7%) and Sturge Weber syndrome (0.7%). Abnormality on MRI was not significantly associated with gender or type of seizure. MR abnormality was observed maximum in patients between 1 to 30 years (30 out of 70 patients i.e. 42.8%) while all the elderly cases showed abnormal MRI, with infract with gliosis being the most common finding. Conclusions : MR imaging should be the first investigation of choice in epileptic syndrome, cerebrovascular disease with seizure, developmental cortical malformations, and vascular malformations.